Perovskite cell and preparation method thereof, laminated cell and photovoltaic module

By using polynorbornene hole transport materials in perovskite solar cells, the problem of low hole mobility of hole transport materials is solved, significantly improving the open circuit voltage and filling factor of the battery, and improving the overall performance.

CN120112052APending Publication Date: 2025-06-06JINKO SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510377701.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The hole mobility of hole transport materials in perovskite solar cells is low, resulting in the impact of battery performance.

Method used

Using hole transport materials based on the polynorbornene main chain structure, two polynorbornene hole transport materials were designed and synthesized by introducing dimethoxytrianiline or dimethylthiotrianiline-substituted carbazole side chain units.

Benefits of technology

It significantly improves hole mobility, reduces the recombination loss during charge transport, reduces series resistance, improves the open circuit voltage and fill factor, and improves the overall performance of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120112052A_ABST
    Figure CN120112052A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite cell, the perovskite cell comprises a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode, and the hole transport layer comprises a hole transport material. The hole transport material is a polynorbornene hole transport material. On the basis of a polynorbornene main chain structure, two polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) are designed and synthesized by introducing a dimethoxytriphenylamine or dimethylthio triphenylamine substituted carbazole side chain unit, and the problems that hole transport materials in perovskite solar cells are low in hole mobility, high in hole transport efficiency and the like are solved. And the performance of the battery is influenced. The invention also provides a method for preparing the perovskite cell, and a laminated cell and a photovoltaic module comprising the perovskite cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of novel hole transport materials for perovskite solar cells, and mainly relates to a perovskite battery, a preparation method thereof, a tandem battery, and a photovoltaic module. Background Art

[0002] Perovskite solar cells (PSCs) have become one of the most remarkable topics in new clean energy because of their impressive high power conversion efficiency in the process of converting solar energy into electrical energy. In the past few years, great progress has been made in PSCs, with the power efficiency increasing from 3.8% to 26.8%. Moreover, they have low manufacturing costs and are easy to commercialize, making them the most promising clean energy to replace silicon-based solar cells at present.

[0003] As a key interface layer of perovskite solar cells (PSCs), the hole transport material undertakes the dual functions of hole selective transport and anode protection. Its mechanism of action is as follows: on the one hand, the HOMO energy level and LUMO energy level of the hole transport material need to match the perovskite layer to facilitate the effective transport of holes and prevent electrons from reaching the anode; on the other hand, the direct contact between the metal anode and the perovskite light-absorbing layer is blocked by a dense film structure to avoid interfacial side reactions. However, there are still significant bottlenecks in the existing hole transport material system - the hole mobility of traditional organic hole transport materials (such as Spiro-OMeTAD) is generally lower than 1×10 -3 cm 2 / Vs, resulting in increased recombination loss and elevated series resistance during the charge transport process, severely restricting the improvement of the open-circuit voltage and fill factor.

[0004] In order to solve the problem that the low hole mobility of the hole transport material in perovskite solar cells affects the battery performance, the present application provides a perovskite battery, a preparation method thereof, a tandem battery, and a photovoltaic module. Summary of the Invention

[0005] In order to solve the problem that the low hole mobility of the hole transport material in perovskite solar cells affects the battery performance, the present application provides a perovskite battery, which includes a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer, and an electrode. The hole transport layer includes a hole transport material, and the hole transport material has the chemical general formula of formula (Ι), where 10 < n < 10000, and A is independently selected from O or S:

[0006]

[0007] Optionally, the structural formula of the hole transport material is any one of the following two:

[0008]

[0009] Polymers based on non-conjugated poly(cis, exo-2,3-diarylnorbornene) backbones (polynorbornene-based) have many advantages, such as: their ROMP ring-opening polymerization process is simple and rapid, the degree of polymerization is high, the material cost is low, and by changing the different functional groups Ar of norbornene, polymers with predetermined properties can be obtained, proposing a new strategy for the development of HTMs.

[0010] First, the ROMP ring-opening polymerization characteristics of polynorbornene-based polymers make them easy to synthesize and can obtain high molecular weight polymers. This characteristic ensures that the hole transport material has good film forming properties and stability, thereby improving the performance of perovskite solar cells; secondly, by changing the different functional groups Ar of norbornene, the properties of the polymer can be flexibly adjusted to obtain hole transport materials with predetermined properties. This controllability provides a broad space for optimizing the performance of hole transport materials, enabling them to better match the needs of perovskite solar cells.

[0011] Taking into account the advantages of the synthesis method of polynorbornene polymers and the controllability of side chain units, this application is based on the polynorbornene main chain structure. By introducing dimethoxytriphenylamine or dimethylthiotriphenylamine substituted carbazole side chain units, two polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) are designed and synthesized. The introduction of these side chain units not only enhances the hole transport ability of the polymer, but also improves its thermal stability and chemical stability.

[0012] PNB-Cz-O and PNB-Cz-S were used as undoped hole transport materials in inverse perovskite devices, achieving remarkable results. These two materials can effectively improve hole mobility and reduce recombination losses during charge transport, thereby reducing series resistance, increasing open circuit voltage and fill factor, and solving the problem of low hole mobility of hole transport materials in perovskite solar cells, which affects battery performance.

[0013] The present application also provides a method for preparing a perovskite battery, which is used to prepare the above-mentioned perovskite battery, comprising the following steps: sequentially stacking the hole transport layer, the perovskite absorption layer, the electron transport layer and the electrode on the transparent conductive substrate. The step of preparing the hole transport layer comprises configuring the above-mentioned hole transport material into a solution and then coating it on the transparent conductive substrate. The method for preparing the hole transport material comprises the following steps:

[0014] S1: mixing norbornene monomer, second-generation Gerbs reagent and organic solvent to obtain a polymerization solution;

[0015] S2: stirring the solution to be polymerized at room temperature for at least 1 hour to obtain a polymerized solution;

[0016] S3: separating the organic layer of the polymer solution, drying it to obtain an eluate, and extracting the eluate with DCM to obtain a solution to be precipitated;

[0017] S4: subjecting the liquid to be precipitated to sedimentation and extraction treatment to obtain a polynorbornene-based polymer, which is the hole transport material;

[0018] The chemical structural formula of the norbornene monomer is:

[0019]

[0020] Optionally, the S1 further includes:

[0021] After the reaction bottle is soaked and cleaned in potassium dichromate washing solution, the salt layer on the inner wall is removed with saturated water vapor, and the reaction bottle is baked in flame and cooled under nitrogen protection to obtain a pre-treated reaction bottle;

[0022] In the pretreatment reaction bottle, a norbornene monomer, a second-generation Gerbs reagent and an organic solvent are mixed to obtain a solution to be polymerized.

[0023] The reaction bottle used in the experiment was treated as above to remove oxygen from the bottle wall. At the same time, the inner wall of the reaction bottle was thoroughly cleaned to reduce the interference of impurities on the chemical reaction, thus ensuring the purity and performance of the reaction product.

[0024] Optionally, the concentration of the norbornene monomer in the polymerization solution is 0.1 to 1.0 mol / L, and the concentration of the second-generation Gerbs reagent in the polymerization solution is 1.0 to 10.0×10 -3 mol / L.

[0025] Optionally, the S1 further includes:

[0026] Under the protection of inert gas, raw material I, monomer I, tetrakis(triphenylphosphine)palladium and potassium carbonate are mixed in a solvent at 80-90°C for 6-12 hours, wherein the solvent is toluene, ethanol and water, wherein the volume ratio of toluene, ethanol and water is 2:1:1. After the reaction, the mixture is cooled to room temperature, extracted with DCM, the organic phase is dried, filtered, and distilled under reduced pressure. After purification and drying, the first product is obtained. The chemical structure of the raw material I is:

[0027]

[0028] The chemical structural formula of the monomer I is:

[0029]

[0030] The chemical structural formula of the first product is:

[0031]

[0032] Under the protection of inert gas, the first product and sodium borohydride are added to THF, and the mixture is reacted at -5 to 0°C for 3 hours. The mixture is extracted with DCM, and the organic phase is dried, filtered, and distilled under reduced pressure. The mixture is allowed to settle and filtered to obtain the second product.

[0033] The chemical structural formula of the second product is:

[0034]

[0035] Under the protection of inert gas, the second product and triethylamine are added to dry THF, and the raw material II is dissolved in dry THF after stirring, and slowly dripped into the mixed reaction system, and reacted at -2 to 0°C for 10 to 16 hours. After quenching with water, saturated sodium chloride solution and dichloromethane are used for extraction, and the organic phase is dried with anhydrous magnesium sulfate, filtered, and distilled under reduced pressure. Finally, it is purified by column chromatography to obtain norbornene monomer. The chemical structure of the raw material II is:

[0036]

[0037] The norbornene monomer, the second-generation Gerbs reagent and the organic solvent are mixed in the pretreatment reaction bottle to obtain a polymerization solution.

[0038] Optionally, the molar ratio of the raw material I, monomer I, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1:(2.2-3):(0.03-0.1):(4-8).

[0039] Optionally, the molar ratio of the first product to sodium borohydride is 1:(8-15).

[0040] Optionally, the molar ratio of the second product, raw material II and triethylamine is 1:(1.1-1.3):(2-3).

[0041] The present application also provides a stacked cell, comprising: a top cell, which is the above-mentioned perovskite cell; and a crystalline silicon bottom cell, which is located on a side of the transparent conductive substrate of the perovskite cell away from the electrode.

[0042] The present application also provides a photovoltaic module, comprising: a plurality of the above-mentioned stacked cells; a connecting component, the connecting component is used to connect adjacent stacked cells; an adhesive film, the adhesive film covers the surface of the stacked cells; and a cover plate, the cover plate is located on the surface of the adhesive film away from the stacked cells.

[0043] The present application provides a perovskite cell, which includes a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode, wherein the hole transport layer includes a hole transport material. The hole transport material is a polynorbornene hole transport material. Based on the main chain structure of polynorbornene, two polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) are designed and synthesized by introducing a carbazole side chain unit substituted with dimethoxytriphenylamine or dimethylthiotriphenylamine, which solves the problem that the hole mobility of the hole transport material in the perovskite solar cell is low, resulting in the problem that the battery performance is affected. The present application also provides a method for preparing the above-mentioned perovskite cell, as well as a stacked cell and a photovoltaic module comprising the above-mentioned perovskite cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0045] Figure 1 A schematic diagram of a battery structure provided in an embodiment of the present application;

[0046] Figure 2 is the H NMR spectrum of PNB-Cz-O;

[0047] Figure 3 is the H NMR spectrum of PNB-Cz-S;

[0048] Figure 4 Schematic diagram of the process for preparing hole transport materials by polymerization of norbornene monomers;

[0049] Figure 5 Schematic diagram of the preparation process of norbornene monomer;

[0050] Figure 6 Schematic diagram of the synthesis route of PNB-Cz-O;

[0051] Figure 7 Schematic diagram of the synthesis route of PNB-Cz-S;

[0052] Figure 8 These are the short-circuit current density-open-circuit voltage curves of perovskite cell one and perovskite cell five. DETAILED DESCRIPTION

[0053] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.

[0054] In order to solve the problem that the hole mobility of the hole transport material in the perovskite solar cell is low, which affects the battery performance, the present application provides a perovskite battery, the perovskite battery includes a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode, the transparent conductive substrate is ITO glass, the electrode includes chromium and gold, and the structure of the perovskite battery is as follows Figure 1 The hole transport layer includes a hole transport material, and the structural formula of the hole transport material is any one of the following two:

[0055]

[0056] Figure 2 is the H NMR spectrum of PNB-Cz-O, Figure 3 This is the H NMR spectrum of PNB-Cz-S.

[0057] Polymers based on non-conjugated poly(cis, exo-2,3-diarylnorbornene) backbones (polynorbornene-based) have many advantages, such as: their ROMP ring-opening polymerization process is simple and rapid, the degree of polymerization is high, the material cost is low, and by changing the different functional groups Ar of norbornene, polymers with predetermined properties can be obtained, proposing a new strategy for the development of HTMs.

[0058] First, the ROMP ring-opening polymerization characteristics of polynorbornene-based polymers make them easy to synthesize and can obtain high molecular weight polymers. This characteristic ensures that the hole transport material has good film forming properties and stability, thereby improving the performance of perovskite solar cells; secondly, by changing the different functional groups Ar of norbornene, the properties of the polymer can be flexibly adjusted to obtain hole transport materials with predetermined properties. This controllability provides a broad space for optimizing the performance of hole transport materials, enabling them to better match the needs of perovskite solar cells.

[0059] Taking into account the advantages of the synthesis method of polynorbornene polymers and the controllability of side chain units, this application is based on the polynorbornene main chain structure. By introducing dimethoxytriphenylamine or dimethylthiotriphenylamine substituted carbazole side chain units, two polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) are designed and synthesized. The introduction of these side chain units not only enhances the hole transport ability of the polymer, but also improves its thermal stability and chemical stability.

[0060] PNB-Cz-O and PNB-Cz-S were used as undoped hole transport materials in inverse perovskite devices, achieving remarkable results. These two materials can effectively improve hole mobility and reduce recombination losses during charge transport, thereby reducing series resistance, increasing open circuit voltage and fill factor, and solving the problem of low hole mobility of hole transport materials in perovskite solar cells, which affects battery performance.

[0061] The polynorbornene hole transport material prepared by the invention has good solubility in solvents such as dimethyl sulfoxide, N,N'-dimethylformamide, toluene, chlorobenzene, dichloromethane, etc., has a high decomposition temperature, and has good thermal stability. At the same time, it has good film-forming properties, good wettability with perovskite precursor solvents, is helpful for the crystallization and film formation of perovskite, has good mobility, is conducive to the extraction and transmission of holes, has a deeper HOMO energy level that matches perovskite, and the raw material cost for preparing the polynorbornene hole transport material is low, the preparation process is simple, and is suitable for industrial production.

[0062] The present application also provides a method for preparing a perovskite battery, which is used to prepare the above-mentioned perovskite battery, comprising the following steps: sequentially stacking a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode on a transparent conductive substrate. The step of preparing the hole transport layer comprises configuring the above-mentioned hole transport material into a solution and then coating it on the transparent conductive substrate. The method for preparing the hole transport material comprises the following steps:

[0063] S1: mixing norbornene monomer, second-generation Gerbs reagent and organic solvent to obtain a polymerization solution;

[0064] S2: stirring the solution to be polymerized at room temperature for at least 1 hour to obtain a polymerized solution;

[0065] S3: separating the organic layer of the polymer solution and drying it to obtain an eluate, and extracting the eluate with DCM to obtain a solution to be precipitated;

[0066] S4: After the liquid to be precipitated is subjected to sedimentation and extraction treatment, a polynorbornene-based polymer is obtained, which is a hole transport material.

[0067] In some embodiments, the method for preparing a hole transport material by polymerization of norbornene monomers is as follows Figure 4 As shown. Under room temperature conditions, the second generation Grubbs catalyst was used to polymerize norbornene monomer IV. The reaction bottle used in the experiment needs to be soaked and cleaned in potassium dichromate solution, then the salt layer on the inner wall is removed with saturated water vapor, and finally baked in a flame and cooled with nitrogen protection to achieve the purpose of removing oxygen on the bottle wall. The concentration of monomer IV is 0.1-1.0 mol / L and the concentration of the second generation Grubbs catalyst is 1.0-10.0×10 - 3 mol / L toluene or tetrahydrofuran solution. At room temperature, add the above solution to the reaction bottle, stir for 1h, and then separate the organic layer. 2 SO 4 After drying, the product was extracted with DCM as the eluent, and the solvent was removed under vacuum. Finally, the product was precipitated in methanol and extracted with acetone as the solvent for three days to obtain a polymer material with a narrow molecular weight distribution.

[0068] In some embodiments, the method for preparing norbornene monomer IV is as follows Figure 5 As shown, the specific steps include:

[0069] Specific description of reaction ⅰ: under the protection of inert gas, raw material Ⅰ, monomer Ⅰ, tetrakis(triphenylphosphine)palladium, potassium carbonate are placed in a solvent, the solvent is toluene, ethanol and water, wherein the volume ratio of toluene, ethanol and water is 2:1:1, the reaction temperature is 80-90°C, and the reaction time is 6-12h. After the reaction, cool to room temperature, extract the mixture with DCM, and anhydrous Mg 2 SO 4 The organic phase is dried, filtered, and distilled under reduced pressure. The crude product is separated and purified by a silica gel chromatography column and dried in vacuo to obtain monomer II. The molar ratio of raw material I, monomer I, tetrakis(triphenylphosphine)palladium, and potassium carbonate is 1:(2.2-3):(0.03-0.1):(4-8).

[0070] Specific description of reaction ii: under the protection of inert gas, monomer II and sodium borohydride were added to THF, and the reaction was first carried out at -5 to 0°C for 3 hours, and then at room temperature for 10 to 16 hours. 50 mL of water was added to quench the reaction, and the mixture was extracted with DCM. 2 SO 4 The organic phase is dried, filtered, and distilled under reduced pressure, and finally precipitated with n-hexane / dichloromethane and filtered to obtain monomer III. The molar ratio of monomer II to sodium borohydride is 1:(8-15).

[0071] Specific instructions for reaction iii: Under the protection of inert gas, add monomer III and triethylamine to dry THF, stir at 0°C for 10 minutes, then dissolve raw material II in dry HTF, slowly drip into the mixed reaction system, and react at -2 to 0°C for 10 to 16 hours. Add water to quench the reaction, extract with saturated sodium chloride solution and dichloromethane, dry the organic phase with anhydrous magnesium sulfate, filter, and distill under reduced pressure, and finally purify by column chromatography to obtain monomer IV. The molar ratio of monomer III, raw material II, and triethylamine is 1: (1.1 to 1.3): (2 to 3).

[0072] In some embodiments, a method for preparing a perovskite solar cell comprises the following steps:

[0073] (1) Cleaning: Use deionized water, acetone and ethanol to ultrasonically clean the ITO glass sheet for 15 to 20 minutes, and then use N 2 The residual solvent on the surface of ITO was blown dry with an air gun, and then oxygen plasma treatment was performed for 10 to 15 minutes, and then the ITO glass sheet was transferred to a nitrogen glove box.

[0074] (2) Preparation of hole transport layer: Weigh 3-15 mg of the above-mentioned polynorbornene hole transport material and completely dissolve it in 1 mL of chlorobenzene solution. Take an appropriate amount of the solution and evenly drop it onto the ITO glass substrate. Spin coat at 4000-5000 rpm for 20-30 seconds, and then anneal at 90-110° C. for 10 minutes to obtain an ITO / hole transport layer substrate.

[0075] (3) Preparation of perovskite layer: The ITO / hole transport layer substrate obtained above was cooled to room temperature, preheated at 130-140°C for 3-5 minutes, 50 μl of perovskite solution was taken to cover the ITO / hole transport layer substrate, spin coated at 3000-5000 rpm for 20-30 seconds, and then annealed at 90-100°C for 10 minutes to obtain ITO / hole transport layer / perovskite substrate. The perovskite solution was prepared by mixing 3-bromo-benzylammonium iodide or 3-chlorobenzylammonium iodide, methylammonium chloride, and lead iodide in DMF and DMSO in a certain molar ratio.

[0076] (4) Preparation of electron transport layer: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μl of the PC61BM solution was taken to cover the ITO / hole transport layer / perovskite substrate, spin coated at 1000 rpm for 30 to 50 seconds, and annealed at 70°C for 10 min to obtain an ITO / hole transport layer / perovskite layer / electron transport layer substrate.

[0077] (5) Preparation of electrodes: The above substrate is placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) are evaporated on the PC61BM layer respectively, thereby obtaining the desired inverse quasi-two-dimensional perovskite solar cell.

[0078] Embodiment 1:

[0079] The synthesis method of PNB-Cz-O is as follows Figure 6 As shown, the specific steps for synthesizing the first PNB-Cz-O are as follows:

[0080] Synthesis of compound 2: Under argon protection, compound 1 (3.84 g, 10 mmol) was weighed and added to a 500 mL three-necked flask, and then 30 mL of dry THF was added. The mixture was cooled to -78 ° C and stirred for 10 min under N2 conditions, and then n-butyl lithium (3.75 mL, 1.00 equiv, 1.6 M in n-hexane) was slowly added dropwise, and the mixture was reacted at -78 ° C for 1 h. Tert-butyl alcohol pinacol borate (2.75 mL) was then added, and the reaction was continued at -78 ° C for 1 h, and finally the mixture was moved to room temperature for 12 h. The reaction was quenched with 50 mL of deionized water, extracted with saturated sodium chloride solution and dichloromethane, and the organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure. Finally, the white solid compound 2 was purified by column chromatography (PE:DCM=15:1) with a yield of 79%.

[0081] Synthesis of compound 4: Under argon protection, compound 3 (2 mmol), compound 2, tetrakis(triphenylphosphine)palladium, and potassium carbonate were weighed and added to a 100 mL two-necked flask. The solvent was toluene, ethanol, and water (in a ratio of 2:1:1). The reaction was carried out at 85°C for 6 hours. After cooling to room temperature, the mixture was extracted with saturated sodium chloride solution and dichloromethane. The organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure. Finally, the mixture was purified by column chromatography (PE:DCM=4:1) to obtain compound 4 as a yellow-green powder with a yield of 85%. The molar ratio of compound 3: compound 2: tetrakis(triphenylphosphine)palladium: potassium carbonate was 1:2.2:0.03:4.

[0082] Synthesis of compound 5: Under argon protection, weigh compound 4 (1 mmol) and add 40 mL of dry THF, stir at 0°C for 10 min, add sodium borohydride into the reaction system three times, stir at 0°C for 3 h, then move into room temperature for 12 h, add 50 mL of water to quench the reaction, use saturated sodium chloride solution and dichloromethane to extract three times, dry the organic phase with anhydrous magnesium sulfate, filter, and distill under reduced pressure, finally precipitate with n-hexane / dichloromethane, and filter to obtain a white solid powder of compound 5 with a yield of 95%. The molar ratio of compound 4 to sodium borohydride is 1:8.

[0083] Synthesis of compound 7: Under argon protection, compound 5 (2 mmol) and triethylamine were added to 30 ml of dry THF, stirred at 0°C for 10 min, and then compound 6 was dissolved in 10 ml of dry THF, slowly added dropwise to the mixed reaction system at 0°C, and reacted for 12 h. 50 mL of water was added to quench the reaction, extracted with saturated sodium chloride solution and dichloromethane, the organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain compound 7 with a yield of 89%. Among them, the molar ratio of compound 5: compound 6: triethylamine was 1:1.1:2.

[0084] The synthesis method of PNB-Cz-O is as follows: under argon protection, compound 7 is dissolved in dry THF, and the second-generation Gerbs reagent is quickly injected into the mixture in the bottle as a catalyst to initiate ring-opening polymerization, wherein the concentration of compound 7 in the tetrahydrofuran solution is 0.1 mol / L, and the concentration of the second-generation Gerbs reagent is 1.0×10 -3 mol / L. After stirring at 25°C for 1 hour, vinyl ethyl ether (0.3 mL) was added to the polymer solution to terminate the polymerization. The reaction mixture was precipitated in an acetone solution, filtered, and dissolved in dichloromethane (50 mL). A hydrogen peroxide solution (10 wt% in water, 75 mL) was added to the solution and stirred at room temperature for 1 hour. The organic layer was separated and extracted, dried with Na2SO4, and then extracted with DCM as the eluent, and the solvent was removed under vacuum. Finally, it was precipitated in methanol again and extracted with acetone as the solvent for three days to obtain the first PNB-Cz-O.

[0085] Embodiment 2:

[0086] The steps for synthesizing the second PNB-Cz-O are basically the same as those in the preparation method of Example 1, except that:

[0087] Synthesis of compound 4: react at 80°C for 10 hours, the molar ratio of compound 3: compound 2: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:2.7:0.07:7, and compound 4 is obtained with a yield of 83%.

[0088] Synthesis of compound 5: Stirring was continued at -5°C for 3 h, and then the mixture was moved to room temperature for reaction for 10 h. The molar ratio of compound 4: sodium borohydride was 1:10, and compound 5 was obtained with a yield of 93%.

[0089] Synthesis of compound 7: slowly drip into the mixed reaction system at -2°C and react for 10 hours. The molar ratio of compound 5: compound 6: triethylamine is 1:1.2:2.5 to obtain compound 7 with a yield of 88%.

[0090] Synthesis method of PNB-Cz-O: The concentration of compound 7 in tetrahydrofuran solution is 0.7 mol / L, and the concentration of the second-generation Gerbs reagent is 6.0×10 -3 mol / L, and diPNB-Cz-O was obtained.

[0091] Embodiment three:

[0092] The steps for synthesizing the third PNB-Cz-O are basically the same as the preparation method of Example 1, except that:

[0093] Synthesis of compound 4: react at 90°C for 12 hours, the molar ratio of compound 3: compound 2: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:3:0.1:8, and compound 4 is obtained with a yield of 87%.

[0094] Synthesis of compound 5: Stirring was continued at -3°C for 3 h, and then the mixture was moved to room temperature for reaction for 16 h. The molar ratio of compound 4: sodium borohydride was 1:15, and compound 5 was obtained with a yield of 97%.

[0095] Synthesis of compound 7: slowly drip into the mixed reaction system at -1°C and react for 16h. The molar ratio of compound 5: compound 6: triethylamine is 1:1.3:3 to obtain compound 7 with a yield of 88%.

[0096] Synthesis method of PNB-Cz-O: The concentration of compound 7 in tetrahydrofuran solution is 1.0 mol / L, the concentration of the second-generation Gerbs reagent is 10.0×10 -3 mol / L, and the third PNB-Cz-O was obtained.

[0097] Comparative Example 1:

[0098] The steps for synthesizing PNB-Cz-O are basically the same as those for Example 1, except that:

[0099] Synthesis of compound 4: react at 85°C for 4 hours, the molar ratio of compound 3: compound 2: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:5:0.02:3, and compound 4 is obtained with a yield of 64%.

[0100] Synthesis of compound 5: Stirring was continued at 0°C for 3 h, and then the mixture was moved to room temperature for reaction for 12 h. The molar ratio of compound 4 to sodium borohydride was 1:7, and compound 5 was obtained with a yield of 71%.

[0101] Synthesis of compound 7: slowly drip into the mixed reaction system at 0°C and react for 12h. The molar ratio of compound 5: compound 6: triethylamine is 1:1:4 to obtain compound 7 with a yield of 78%.

[0102] Synthesis method of PNB-Cz-O: The concentration of compound 7 in tetrahydrofuran solution is 2.0 mol / L, and the concentration of the second-generation Gerbs reagent is 0.6×10 -3 mol / L, and the comparative PNB-Cz-O was obtained.

[0103] Embodiment 4:

[0104] The synthesis method of PNB-Cz-S is as follows Figure 7 As shown, the specific steps for synthesizing the first PNB-Cz-S are as follows:

[0105] Synthesis of compound 9: Under argon protection, compound 8 (4.17 g, 10 mmol) was weighed and added to a 500 mL three-necked flask, and then 30 mL of dry THF was added. The mixture was cooled to -78 °C and stirred for 10 min under N2 conditions, and then n-butyl lithium (3.75 mL, 1.00 equiv, 1.6 M in n-hexane) was slowly added dropwise, and the mixture was reacted at -78 °C for 1 hour. Then tert-butyl alcohol pinacol borate (2.75 mL, 15 mmol) was added, and the reaction was continued at -78 °C for 1 hour, and finally the mixture was moved to room temperature for 12 hours. The reaction was quenched with 50 mL of deionized water, extracted with saturated NaCl solution and DCM, and the organic phase was anhydrous MgCl was added. 2 SO 4 The residue was dried, filtered, and finally purified by column chromatography (PE:DCM=15:1) to obtain a white solid compound 9 with a yield of 76%.

[0106] Synthesis of compound 10: Under argon protection, compound 3 (2 mmol), compound 9, tetrakis(triphenylphosphine)palladium, and potassium carbonate were weighed and added to a 100 mL two-necked flask. The solvent was toluene, ethanol, and water (in a ratio of 2:1:1). The reaction was carried out at 85°C for 6 hours. After cooling to room temperature, the mixture was extracted with saturated sodium chloride solution and dichloromethane. The organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure. Finally, the mixture was purified by column chromatography (PE:DCM=4:1) to obtain compound 10 with a yield of 84%. The molar ratio of compound 3: compound 9: tetrakis(triphenylphosphine)palladium: potassium carbonate was 1:2.2:0.03:4.

[0107] Synthesis of compound 11: Under argon protection, compound 10 (1 mmol) was weighed and added to 40 mL of dry THF, stirred at 0°C for 10 min, sodium borohydride was added to the reaction system in three portions, stirred at 0°C for 3 h, then moved to room temperature for 12 h, 50 mL of water was added to quench the reaction, saturated sodium chloride solution and dichloromethane were used to extract three times, the organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure, and finally precipitated with n-hexane / dichloromethane and filtered to obtain a white solid powder of compound 11 with a yield of 91%. The molar ratio of compound 10: sodium borohydride was 1:8.

[0108] Synthesis of compound 12: Under argon protection, compound 11 (2 mmol) and triethylamine were added to 30 ml of dry THF, stirred at 0°C for 10 min, and then compound 6 was dissolved in 10 ml of dry THF and slowly dripped into the mixed reaction system at 0°C for 12 h. 50 mL of water was added to quench the reaction, extracted with saturated sodium chloride solution and dichloromethane, the organic phase was dried over anhydrous magnesium sulfate, filtered, and distilled under reduced pressure, and finally purified by column chromatography (PE:DCM=6:1) to obtain compound 12 with a yield of 87%. The molar ratio of compound 11: compound 6: triethylamine was 1:1.1:2.

[0109] The synthesis method of PNB-Cz-S is as follows: under argon protection, compound 12 is dissolved in dry THF, and the second-generation Grubbs catalyst is quickly injected into the mixture in the bottle to initiate ring-opening polymerization, wherein the concentration of compound 12 in the tetrahydrofuran solution is 0.1 mol / L, and the concentration of the second-generation Grubbs reagent is 1.0×10 -3 mol / L. After stirring at 25°C for 1 hour, vinyl ethyl ether (0.3 mL) was added to the polymer solution to terminate the polymerization. The reaction mixture was precipitated in acetone solution, filtered, and dissolved in dichloromethane (50 mL). Hydrogen peroxide solution (10 wt% in water, 75 mL) was added to the solution and stirred at room temperature for 1 hour. The organic layer was separated and extracted with Na 2 SO 4 After drying, the product was extracted with DCM as the eluent, and the solvent was removed under vacuum. Finally, the product was precipitated in methanol and extracted with acetone as the solvent for three days to obtain the first PNB-Cz-S.

[0110] Embodiment five:

[0111] The steps for synthesizing the second PNB-Cz-S are basically the same as those of the preparation method of Example 4, except that:

[0112] Synthesis of compound 10: react at 80°C for 10 hours, the molar ratio of compound 3: compound 9: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:2.7:0.07:7, and compound 10 is obtained with a yield of 82%.

[0113] Synthesis of compound 11: Stirring was continued at -5°C for 3 h, and then the mixture was moved to room temperature for reaction for 10 h. The molar ratio of compound 10: sodium borohydride was 1:10, and compound 11 was obtained with a yield of 90%.

[0114] Synthesis of compound 12: slowly drip into the mixed reaction system at -2°C and react for 10 hours. The molar ratio of compound 11: compound 6: triethylamine is 1: 1.2: 2.5 to obtain compound 12 with a yield of 90%.

[0115] Synthesis method of PNB-Cz-S: The concentration of compound 12 in tetrahydrofuran solution is 0.7 mol / L, and the concentration of the second-generation Gerbs reagent is 6.0×10 -3 mol / L, and obtained diPNB-Cz-S.

[0116] Embodiment six:

[0117] The steps for synthesizing the third PNB-Cz-S are basically the same as those of the preparation method of Example 4, except that:

[0118] Synthesis of compound 10: react at 90°C for 12 hours, the molar ratio of compound 3: compound 9: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:3:0.1:8, and compound 10 is obtained with a yield of 88%.

[0119] Synthesis of compound 11: Stirring was continued at -3°C for 3 h, and then the mixture was moved to room temperature for reaction for 16 h. The molar ratio of compound 10: sodium borohydride was 1:15, and compound 11 was obtained with a yield of 96%.

[0120] Synthesis of compound 12: slowly drip into the mixed reaction system at -1°C and react for 16h. The molar ratio of compound 11: compound 6: triethylamine is 1:1.3:3 to obtain compound 12 with a yield of 86%.

[0121] Synthesis method of PNB-Cz-S: The concentration of compound 12 in tetrahydrofuran solution is 1.0 mol / L, the concentration of the second-generation Gerbs reagent is 10.0×10 -3 mol / L, and the third PNB-Cz-S was obtained.

[0122] Comparative Example 2:

[0123] The steps for synthesizing comparative PNB-Cz-S are basically the same as those of the preparation method of Example 1, and the difference from Example 4 is that:

[0124] Synthesis of compound 10: react at 85°C for 4 hours, the molar ratio of compound 3: compound 9: tetrakis(triphenylphosphine)palladium: potassium carbonate is 1:5:0.02:3, and compound 10 is obtained with a yield of 69%.

[0125] Synthesis of compound 11: Stirring was continued at 0°C for 3 h, and then the mixture was moved to room temperature for reaction for 12 h. The molar ratio of compound 10: sodium borohydride was 1:7, and compound 11 was obtained with a yield of 79%.

[0126] Synthesis of compound 12: slowly drip into the mixed reaction system at 0°C and react for 12h. The molar ratio of compound 11: compound 6: triethylamine is 1:1:4 to obtain compound 7 with a yield of 80%.

[0127] Synthesis method of PNB-Cz-S: The concentration of compound 12 in tetrahydrofuran solution is 2.0 mol / L, and the concentration of the second-generation Gerbs reagent is 0.6×10 -3 mol / L, and obtained the comparative PNB-Cz-S.

[0128] The hole mobility of PNB-Cz-O and PNB-Cz-S was evaluated, and the hole mobility of the first PNB-Cz-O, the second PNB-Cz-O, the third PNB-Cz-O, the comparative PNB-Cz-O, the first PNB-Cz-S, the second PNB-Cz-S, the third PNB-Cz-S and the comparative PNB-Cz-S was tested by the space charge limited current method. 3 The thickness of each layer of the single hole device with Ag / Si was determined by a step profiler. The JV characteristic curve of the device was obtained by a Keithley 2450 Source-Measure instrument under dark conditions.

[0129] In contrast, the hole mobility of PNB-Cz-O is 2.91×10 -4 cm 2 ·V -1 ·S -1 , compared with the hole mobility of PNB-Cz-S which is 3.42 cm 2 ·V -1 ·S -1 The curve was subjected to nonlinear fitting analysis, and the average values ​​of the hole mobilities of the first PNB-Cz-O, the second PNB-Cz-O, the third PNB-Cz-O, the first PNB-Cz-S, the second PNB-Cz-S, and the third PNB-Cz-S were calculated. The average values ​​of the hole mobilities of the products PNB-Cz-O and PNB-Cz-S were obtained as shown in Table 1.

[0130] Table 1 Hole mobility of PNB-Cz-O and PNB-Cz-S

[0131]

[0132]

[0133] Experimental results show that both PNB-Cz-O and PNB-Cz-S have excellent hole mobility. Applying them in perovskite solar cells can solve the problem that the battery performance is affected by the low hole mobility of hole transport materials in perovskite solar cells.

[0134] In comparison, the hole mobility of PNB-Cz-S is higher than that of PNB-Cz-O, and the hole mobility of the comparative PNB-Cz-O and the comparative PNB-Cz-S is significantly worse than that of the first PNB-Cz-O, the second PNB-Cz-O, the third PNB-Cz-O, the first PNB-Cz-S, the second PNB-Cz-S, and the third PNB-Cz-S. Specifically, the average hole mobility of PNB-Cz-S is about 19% higher than that of PNB-Cz-O. This indicates that in similar molecular structures, the introduction of sulfur (S) atoms may help improve hole mobility, and sulfur atoms have advantages in improving hole transport performance compared to oxygen (O) atoms.

[0135] Embodiment seven:

[0136] Preparation of perovskite battery 1:

[0137] (1) Cleaning: The ITO glass sheet was ultrasonically cleaned with deionized water, acetone, and ethanol for 15 minutes in sequence. The residual solvent on the surface of the ITO was then blown dry with a N2 air gun. The ITO glass sheet was then treated with oxygen plasma for 10 minutes. The ITO glass sheet was then transferred to a nitrogen glove box.

[0138] (2) Preparation of hole transport layer: Weigh 3 mg of the first PNB-Cz-O and completely dissolve it in 1 mL of chlorobenzene solution. Take an appropriate amount of the solution and evenly add it onto the ITO glass substrate. Spin coat at 4000 rpm for 20 seconds, and then anneal at 90°C for 10 minutes to obtain an ITO / hole transport layer substrate.

[0139] (3) Preparation of perovskite layer: The ITO / hole transport layer substrate obtained above was cooled to room temperature, preheated at 130°C for 3 minutes, 50 μl of perovskite solution was taken to cover the ITO / hole transport layer substrate, spin coated at 3000 rpm for 20 seconds, and then annealed at 90°C for 10 minutes to obtain ITO / hole transport layer / perovskite substrate. The perovskite solution was prepared by mixing 3-bromo-benzylammonium iodide, methylammonium chloride, and lead iodide in DMF and DMSO.

[0140] (4) Preparation of electron transport layer: The ITO / hole transport layer / perovskite substrate obtained above was cooled to room temperature, PC61BM was prepared into a 15 mg / mL solution, and then 40 μl of the PC61BM solution was taken to cover the ITO / hole transport layer / perovskite substrate, and spin coated at 1000 rpm for 30 seconds to obtain an ITO / hole transport layer / perovskite layer / electron transport layer substrate.

[0141] (5) Preparation of electrodes: The above substrate was placed in a vacuum evaporation chamber, and Cr (6 nm) and Au (80 nm) were evaporated on the PC61BM layer respectively, thereby obtaining a perovskite cell.

[0142] Embodiment eight:

[0143] Preparation of perovskite battery 2: The steps of preparing perovskite battery 2 are basically the same as those of Example 7, except that:

[0144] In (1), the ITO glass sheet was ultrasonically cleaned for 20 minutes and subjected to oxygen plasma treatment for 15 minutes.

[0145] In (2), 15 mg of the second PNB-Cz-O was weighed, spin-coated at 5000 rpm for 30 seconds, and annealed at 110° C. for 10 minutes.

[0146] In (3), preheat at 140°C for 5 minutes, take 50 μl of the perovskite solution to cover the ITO / hole transport layer substrate, spin coat at 5000 rpm for 30 seconds, and then anneal at 100°C for 10 minutes.

[0147] In (4), spin coating was performed at 1000 rpm for 50 seconds.

[0148] Embodiment nine:

[0149] Preparation of perovskite battery 3: The steps of preparing perovskite battery 3 are basically the same as those of Example 7, except that:

[0150] In (1), the ITO glass sheet was ultrasonically cleaned for 17 minutes and subjected to oxygen plasma treatment for 13 minutes.

[0151] In (2), 12 mg of the third PNB-Cz-O was weighed, spin-coated at 4500 rpm for 27 seconds, and annealed at 100° C. for 10 minutes.

[0152] In (3), the substrate was preheated at 135°C for 4 minutes, 50 μl of the perovskite solution was spread over the ITO / hole transport layer substrate, spin-coated at 3500 rpm for 25 seconds, and then annealed at 97°C for 10 minutes.

[0153] In (4), spin coating was performed at 1000 rpm for 35 seconds.

[0154] Comparative Example 3:

[0155] A comparative perovskite cell 1 is prepared. The steps for preparing the comparative perovskite cell 1 are basically the same as the method steps of Example 9, except that the hole transport material in step (2) is replaced with comparative PNB-Cz-O to obtain a comparative perovskite cell 1.

[0156] Embodiment ten:

[0157] The hole transport material in step (2) of the method of Example 7 is replaced with the first PNB-Cz-S to obtain perovskite cell 4.

[0158] Embodiment eleven:

[0159] The hole transport material in step (2) of the method of Example 7 is replaced with the second PNB-Cz-S to obtain perovskite cell 5.

[0160] Embodiment 12:

[0161] The hole transport material in step (2) of the method of Example 7 is replaced with the third PNB-Cz-S to obtain perovskite cell 6.

[0162] Comparative Example 4:

[0163] The hole transport material in step (2) of the method of Example 7 was replaced with a comparative PNB-Cz-S to prepare a comparative perovskite cell 2.

[0164] Under AM 1.5G lighting conditions, the speed is 0.02V s -1 The performance of perovskite cells 1 to 6, comparison perovskite cell 1 and comparison perovskite cell 2 were measured by forward and reverse scanning. The detailed photovoltaic indexes of open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE) are shown in Table 2. The short circuit current density-open circuit voltage curve of the best device is shown in Figure 8 As shown, they are perovskite cell one and perovskite cell five.

[0165] Table 2 Battery performance test results

[0166] Battery Photoelectric conversion efficiency / % Open circuit voltage / V <![CDATA[Short - circuit current / mA·cm -2 > Fill factor / % Perovskite battery 1 17.41 1.20 19.92 72.71 Perovskite battery 2 17.20 1.21 19.80 71.50 Perovskite battery three 17.30 1.20 19.75 72.00 Comparison of perovskite batteries 12.00 1.05 15.00 60.00 Perovskite battery 4 18.20 1.18 20.10 75.00 Perovskite battery 5 18.42 1.19 20.20 75.74 Perovskite battery VI 18.30 1.18 20.15 75.50 Comparison of perovskite batteries 11.80 1.04 14.80 59.50

[0167] The test results show that the perovskite cells using the hole transport materials of the present application have excellent performance in key performance indicators such as photoelectric conversion efficiency (PCE), open circuit voltage (Voc), short circuit current density (Jsc) and fill factor (FF). Moreover, the indicators of perovskite cells four, five and six are better than those of perovskite cells one, two and three, that is, in the cells using the hole transport materials of the present application, the PNB-Cz-S material containing sulfur atom substituents (S) shows a trend slightly better than the PNB-Cz-O material containing oxygen atom substituents (O). In contrast, the perovskite cells prepared using the comparative hole transport materials (comparative perovskite cell one and comparative perovskite cell two) performed poorly in all performance indicators.

[0168] Specifically, the photoelectric conversion efficiency of perovskite cells 4, 5, and 6 all exceeded 18%, with perovskite cell 5 reaching the highest value of 18.42%. These cells also showed high levels in short-circuit current density and open-circuit voltage, with short-circuit current density at 20 mA cm -2 The open circuit voltage is between 1.18 V and 1.21 V. The fill factor is also generally high, indicating that the charge transfer and collection efficiency inside the battery is high.

[0169] The experimental results show that the perovskite cells prepared using the polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) provided in this application have excellent performance in key performance indicators such as photoelectric conversion efficiency, open circuit voltage, short circuit current density and fill factor. This fully proves the effectiveness of the hole transport materials in this application in solving the technical problem of low hole mobility of hole transport materials in perovskite solar cells. By introducing the carbazole side chain unit substituted with dimethoxytriphenylamine or dimethylthiotriphenylamine, the hole transport material designed in this application significantly enhances the hole transport ability of the polymer, thereby improving the overall performance of the perovskite solar cell.

[0170] The present application also provides a stacked cell, comprising: a top cell, which is the above-mentioned perovskite cell; and a crystalline silicon bottom cell, which is located on a side of the transparent conductive substrate of the perovskite cell away from the electrode.

[0171] Tandem cells usually stack two or more different types of solar cells (such as perovskite cells and crystalline silicon cells) to take advantage of their respective absorption advantages in different spectral ranges, thereby improving the photoelectric conversion efficiency of the entire photovoltaic system.

[0172] Crystalline silicon bottom cells refer to solar cells that use crystalline silicon as the substrate material. Crystalline silicon includes monocrystalline silicon and polycrystalline silicon, and is one of the most commonly used materials in solar cells. Crystalline silicon bottom cells have high photoelectric conversion efficiency, good stability and long service life. Different technical routes and structures (such as PERC, TOPCon, HJT, etc.) can be implemented on crystalline silicon substrates to meet different application requirements. The full name of PERC cell is "emitter and back passivation cell". PERC cells improve the light absorption and electron collection efficiency on the back of the cell by introducing a silicon oxide film on the back of the cell, thereby improving the photoelectric conversion efficiency of the cell. The full name of TOPCon cell is "tunnel oxide passivation contact cell", which is a solar cell using tunnel oxide passivation contact. It reduces surface defects by adding an oxide layer, improves the electron lifetime and carrier collection efficiency, and also has good stability and a long service life. The full name of HJT cell is "intrinsic thin film heterojunction cell", which is a solar cell using a heterostructure and an extremely thin intrinsic layer. HJT cell combines the advantages of traditional silicon-based solar cells and organic thin-film solar cells, with high conversion rate, low temperature coefficient and long service life. It adopts a design with reduced battery thickness and multi-layer structure, which can provide more stable power output in high temperature and low light environments.

[0173] When sunlight shines on the stacked cells, the perovskite cells first absorb short-wavelength photons and generate photogenerated carriers (electrons and holes), which are then collected on the electrodes of the top cells through the electron transport layer and the hole transport layer. At the same time, the crystalline silicon cells absorb long-wavelength photons and generate corresponding photogenerated carriers, which are also collected on the electrodes of the bottom cells.

[0174] In some embodiments, the tandem cell further comprises a top cell and an amorphous silicon bottom cell.

[0175] The present application also provides a photovoltaic module, comprising: a plurality of the above-mentioned laminated cells; a connecting component, the connecting component is used to connect adjacent laminated cells; an adhesive film, the adhesive film covers the surface of the laminated cells; and a cover plate, the cover plate is located on the surface of the adhesive film away from the laminated cells.

[0176] The present application provides a perovskite cell, which includes a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode, wherein the hole transport layer includes a hole transport material. The hole transport material is a polynorbornene hole transport material. Based on the main chain structure of polynorbornene, two polynorbornene hole transport materials (PNB-Cz-O and PNB-Cz-S) are designed and synthesized by introducing a carbazole side chain unit substituted with dimethoxytriphenylamine or dimethylthiotriphenylamine, which solves the problem that the hole mobility of the hole transport material in the perovskite solar cell is low, resulting in the problem that the battery performance is affected. The present application also provides a method for preparing the above-mentioned perovskite cell, as well as a stacked cell and a photovoltaic module comprising the above-mentioned perovskite cell.

[0177] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.

Claims

1. A perovskite battery, characterized in that: The perovskite cell comprises a transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and an electrode, wherein the hole transport layer comprises a hole transport material, and the hole transport material has a chemical formula (I): Among them, 10 <n <10000, A is independently selected from O or S.

2. A method for preparing a perovskite battery, for preparing the perovskite battery according to claim 1, characterized in that: The following steps are involved: The hole transport layer, the perovskite absorption layer, the electron transport layer and the electrode are sequentially stacked on the transparent conductive substrate, wherein the step of preparing the hole transport layer comprises preparing the hole transport material according to claim 1 into a solution and then coating it on the transparent conductive substrate, and the method for preparing the hole transport material comprises the following steps: S1: mixing norbornene monomer, second-generation Gerbs reagent and organic solvent to obtain a polymerization solution; S2: stirring the solution to be polymerized at room temperature for at least 1 hour to obtain a polymerized solution; S3: separating the organic layer of the polymer solution, drying it to obtain an eluate, and extracting the eluate with DCM to obtain a solution to be precipitated; S4: subjecting the liquid to be precipitated to sedimentation and extraction treatment to obtain a polynorbornene-based polymer, which is the hole transport material; The chemical structural formula of the norbornene monomer is:

3. The method for preparing a perovskite battery according to claim 2, characterized in that: The S1 further comprises: After the reaction bottle is soaked and cleaned in potassium dichromate washing solution, the salt layer on the inner wall is removed with saturated water vapor, and the reaction bottle is baked in flame and cooled under nitrogen protection to obtain a pre-treated reaction bottle; In the pretreatment reaction bottle, a norbornene monomer, a second-generation Gerbs reagent and an organic solvent are mixed to obtain a polymerization solution.

4. The method for preparing a perovskite battery according to claim 2, characterized in that: The concentration of the norbornene monomer in the polymerization solution is 0.1-1.0 mol / L, and the concentration of the second-generation Gerbs reagent in the polymerization solution is 1.0-10.0×10 -3 mol / L.

5. The method for preparing a perovskite battery according to claim 2, characterized in that: The S1 further comprises: Under the protection of inert gas, raw material I, monomer I, tetrakis(triphenylphosphine)palladium and potassium carbonate are mixed in a solvent at 80-90°C for 6-12 hours, wherein the solvent is toluene, ethanol and water, wherein the volume ratio of toluene, ethanol and water is 2:1:

1. After the reaction, the mixture is cooled to room temperature, extracted with DCM, the organic phase is dried, filtered, and distilled under reduced pressure. After purification and drying, the first product is obtained. The chemical structure of the raw material I is: The chemical structural formula of the monomer I is: The chemical structural formula of the first product is: Under the protection of inert gas, the first product and sodium borohydride are added to THF, and the mixture is reacted at -5 to 0°C for 3 hours. The mixture is extracted with DCM, and the organic phase is dried, filtered, and distilled under reduced pressure. The mixture is allowed to settle and filtered to obtain the second product. The chemical structural formula of the second product is: Under the protection of inert gas, the second product and triethylamine are added to dry THF, and the raw material II is dissolved in dry THF after stirring, and slowly dripped into the mixed reaction system, and reacted at -2 to 0°C for 10 to 16 hours. After quenching with water, saturated sodium chloride solution and dichloromethane are used for extraction, and the organic phase is dried with anhydrous magnesium sulfate, filtered, and distilled under reduced pressure. Finally, it is purified by column chromatography to obtain norbornene monomer. The chemical structure of the raw material II is: The norbornene monomer, the second-generation Gerbs reagent and the organic solvent are mixed in the pretreatment reaction bottle to obtain a polymerization solution.

6. The method for preparing a perovskite battery according to claim 2, characterized in that: The molar ratio of the raw material I, the monomer I, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1:(2.2-3):(0.03-0.1):(4-8).

7. The method for preparing a perovskite battery according to claim 2, characterized in that: The molar ratio of the first product to sodium borohydride is 1:(8-15).

8. The method for preparing a perovskite battery according to claim 2, characterized in that: The molar ratio of the second product, raw material II and triethylamine is 1:(1.1-1.3):(2-3).

9. A laminated battery, characterized in that: include: A top cell, wherein the top cell is the perovskite cell according to claim 1; A crystalline silicon bottom cell, wherein the crystalline silicon bottom cell is located on a side of the transparent conductive substrate of the perovskite cell away from the electrode.

10. A photovoltaic module, characterized in that: include: A plurality of stacked batteries as claimed in claim 9; A connecting component, the connecting component is used to connect adjacent stacked batteries; An adhesive film, the adhesive film covers the surface of the laminated battery; A cover plate is located on a surface of the adhesive film away from the laminated battery.